2017
DOI: 10.1080/19476337.2017.1321587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermosonication on pathogenic bacteria, quality attributes and stability of soursop nectar during cold storage

Abstract: 2017) Effect of thermosonication on pathogenic bacteria, quality attributes and stability of soursop nectar during cold storage, CyTA -Journal of Food, 15:4, 592-600, ABSTRACTIn this work, the effect of the thermosonication (TS) on the inactivation of Escherichia coli and Staphylococcus aureus in soursop nectar was evaluated, as well as the quality and stability of the nectar during its storage at 4°C. A reduction of 4.5-5 log CFU/mL was achieved with the TS treatment (24 kHz, average temperature of 50-51°C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(48 reference statements)
6
15
0
Order By: Relevance
“…During storage at 10 and 25°C, significant differences in titratable acidity were observed between the control and the stored juice after10 and 2 weeks, respectively. An increase in titratable acidity has also been observed in other fruit juices during storage (Anaya-Esparza et al, 2017;Bull et al, 2004;Chia et al, 2012). The changes in total soluble solids of soursop juice during storage is shown in Figure 4.…”
Section: Effect Of Storage Temperature On Ph Titratable Acidity and mentioning
confidence: 74%
See 1 more Smart Citation
“…During storage at 10 and 25°C, significant differences in titratable acidity were observed between the control and the stored juice after10 and 2 weeks, respectively. An increase in titratable acidity has also been observed in other fruit juices during storage (Anaya-Esparza et al, 2017;Bull et al, 2004;Chia et al, 2012). The changes in total soluble solids of soursop juice during storage is shown in Figure 4.…”
Section: Effect Of Storage Temperature On Ph Titratable Acidity and mentioning
confidence: 74%
“…Storage temperature have been observed to have a variable effect on the total phenolic content and total antioxidant capacity of fruit juices. The phenolic content of pineapple juice remained relatively unchanged during 13 weeks of storage (Chia et al, 2012); however, decreases were observed in soursop nectar (Anaya-Esparza et al, 2017). It is possible that the total phenolic content of the soursop juice remained relatively unchanged due to the inactivation of peroxidase during pasteurization (Odriozola-Serrano et al, 2008).…”
Section: Effect Of Storage Temperature On Nutritional Quality Of Sourmentioning
confidence: 99%
“…The lethality of the inoculated microorganisms was assessed as the difference of initial and final count of the logarithm of CFU/ml (log No‐ log N) of the microorganisms at specified treatment condition of PS (92°C/35 s) and TS (50°C/21 min) (Anaya‐Esparza et al, ). The initial population of E. coli and S. cerevisiae in khoonphal juice was 5.183 and 5.934 log CFU/ml, respectively after inoculation in sterilized khoonphal juice (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the lethality of the microorganisms as a result of the processing, the method described by Anaya‐Esparza et al () was used. Lethality of E. coli was calculated as the difference between the log of colony counts in TSA before and after processing (PS and TS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation